Synopsis of the Central Asian Salvia species with identification key - Turdiboev, Obidjon A.; Shormanova, Aijamal A.; Sheludyakova, Mariya B.; Akbarov, Feruz; Drew, Bryan T.; Celep, Ferhat (Phytotaxa, 2022)
The genus Salvia is comprised of about 1000 species and has diversity hotspots in the Americas, East Asia, southwest Asia and the Mediterranean region. Central Asia also possesses considerable Salvia species diversity but is understudied relative to the aforementioned diversity hotspots. To help remedy this deficiency, we present a synopsis of Central Asian Salvia species based on extensive fieldwork, herbarium consultation, and literature surveys focusing on Uzbekistan, Kyrgyzstan, Tajikistan, Kazakhstan, and Turkmenistan (i.e., Central Asia). According to our final taxonomic revision, there are 41 species of native Salvia in the flora of Central Asia, 24 of which are endemic. Salvia ariana from Tajikistan and S. spinosa from Kazakhstan are documented from the respective countries for the first time, and the presence of S. tianschanica from Tajikistan and S. verticillata from Kazakhstan has been confirmed. In addition, the neotypification of S. deserta and three lectotypifications (Perovskia abrotanoides, S. bucharica and S. trautvetterii) are provided. Furthermore, we synonymized six species of Salvia that were previously reported from Central Asia, including S. intercedens, S. kopetdaghensis, S. linczevskii, S. lipskyi, S. semilanata and S. stepposa. Finally, a new species identification key for Central Asian Salvia is presented based on the new nomenclature changes and our taxonomic revision.